Mobile application for bidding durians - Law, Check Yee; Sek, Yong Wee; Tay, Choo Chuan; Liew, Tze-Hui; Loh, Ya-Qin (2023)
Normally, there are intermediaries between durian farmers and the end consumers. As a result, the retail durian price in the market is generally twice the farm price. As durians are perishable and taste best when they are fresh, intermediaries are necessary in the distribution channel. This is because the production volume per single farmer is not large, and reaching the downstream customers would require a well-planned logistics and suitable transportation as well as strong marketing strategies and networking. With the popularization of the Internet, online bidding is suitable for both durian buyers and sellers. This paper presents the design and development of a mobile application to facilitate the process of selling and bidding durians known as BidDurian. A complete prototype testing has been conducted and the prototype performs well. Future enhancement may include the live video streaming auction function and inclusion of data analytics.